Managing Financial Life: Examining the Factors Impacting the Financial Literacy of Indonesian Students Studying Abroad - Heriyati, Pantri; Antonio, Louis; Soliman, Mohammad (Journal of Indonesian Economy and Business, 2024)
Introduction/Main Objectives: The number of Indonesian students who study abroad has expanded significantly during the past few decades. Nonetheless, the nation has a lot of variables that would assist in the growth of overseas students leaving the country in the future. Consequently, this study aims to investigate the variables influencing the financial literacy of Indonesian students participating in international exchange programs. This study empirically examines how students' financial behavior could be affected by their financial knowledge, financial attitude, and financial culture. It also tests how financial literacy can be directly influenced by financial behavior. Additionally, the mediating role of financial behavior has been evaluated. Background Problems: Notwithstanding the rise in the number of students enrolled in international programs, and the availability of such programs in educational institutions worldwide, these students will confront numerous obstacles and difficulties. A vital skill for these students to possess is financial literacy, since there is a lot of emphasis on cost-saving when pursuing higher education in a global setting. However, studies into financial literacy are noticeably lacking, particularly in emerging nations such as Indonesia. Novelty: The current paper adds to the limited studies concerning the financial life of international students by developing an integrated framework to examine the most crucial factors impacting the financial literacy of Indonesian students participating in international exchange programs. Research Methods: An online survey was conducted to gather the primary data from the respondents. The acquired data were analyzed using PLS-SEM. Finding/Results: The research findings showed that financial literacy was significantly impacted by financial behavior, which in turn was impacted by financial knowledge, financial attitudes, and financial culture. The relationship between financial knowledge, financial attitudes, financial culture, and financial literacy was found to be significantly mediated by financial behavior. Conclusion: The present work provides theoretical and managerial contributions regarding managing the financial life of international students in Indonesia.